Neurohypophyseal hormones: novel actors of striated muscle development and homeostasis - Alessandra Costa; Eleonora Rossi; Bianca Maria Scicchitano; Dario Coletti; Viviana Moresi; Sergio Adamo (PAGEPress Publications, 2014)
Since the 1980's, novel functional roles of the neurohypophyseal hormones vasopressin and oxytocin have emerged. Several studies have investigated the effects of these two neurohormones on striated muscle tissues, both in vitro and in vivo. The effects of vasopressin on skeletal myogenic cells, developing muscle and muscle homeostasis have been documented. Oxytocin appears to have a greater influence on cardiomyocite differentiation and heart homeostasis. This review summarizes the studies on these novel roles of the two neurohypophyseal hormones, and open the possibility of new therapeutic approaches for diseases affecting striated muscle.